Direct Comparison of Real-world Effectiveness of Biologics for Psoriasis using Absolute and Relative Psoriasis Area and Severity Index Scores in a Prospective Multicentre Cohort - Marloes E. van Muijen; Sarah E. Thomas; Hans M.M. Groenewoud; Marisol E. Otero; Paul M. Ossenkoppele; Marcellus D. Njoo; Sharon R.P. Dodemont; Else N. Kop; Maartje A.M. Berends; Marjolein I.A. Koetsier; Johannes M. Mommers; John E.M. Körver; et al. (Acta Dermato-Venereologica, 2022)
Real-world evidence, directly comparing the effectiveness of interleukin (IL)17-inhibitors, IL23-inhibitors, tumour necrosis factor alpha (TNF-α)-inhibitors and an IL12/23-inhibitor in psoriasis, is scarce. The aim of this study was to directly compare the first-year effectiveness of biologic therapies for psoriasis, corrected for confounders. This prospective, multicentre cohort study assessed BioCAPTURE data on etanercept, adalimumab, ustekinumab, secukinumab, ixekizumab, and guselkumab in 1,080 treatment episodes of 700 patients with psoriasis. The course of the mean absolute Psoriasis Area and Severity Index (PASI) and the proportion of patients who achieved PASI90/PASI75 were compared using linear mixed models and mixed logistic regression models respectively, corrected for baseline PASI, biologic naivety, and weight. Patients treated with adalimumab, ustekinumab, secukinumab, ixekizumab, or guselkumab all had a significantly lower mean PASI after 12 months compared with etanercept, and significantly higher overall odds of reaching PASI90 than those treated with etanercept. Patients treated with ixekizumab or guselkumab also had higher probabilities of reaching PASI90 than adalimumab, ustekinumab, and secukinumab. Relative to randomized controlled trials, the proportions of patients who reached PASI90/75 were lower in this real-world study.